Connectors for electronic equipment. Printed board connectors with assessed quality. Detail specification for cable-to-board connectors, with a modular pitch of 25 mm and integrated shielding function, applicable for transverse packing density of 15 mm, having a basic grid of 2, 5 mm in accordance with IEC 60917-1 Part 4-108, (2nd June 2003) - British Standards Institution,
No abstract available